2009
DOI: 10.48550/arxiv.0907.1232
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stanley depth of square free Veronese ideals

Abstract: We compute the Stanley depth for the quotient ring of a square free Veronese ideal and we give some bounds for the Stanley depth of a square free Veronese ideal. In particular, it follows that both satisfy the Stanley's conjecture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…This formula was later confirmed by Biró, Howard, Keller, Trotter and Young in [4] using combinatorial techniques upon which this paper builds. The Stanley depth of I n,d in the other situation remains unexplored in general, although Cimpoeas ¸considered a similar problem in [7]. In this paper, we prove an exact formula for the Stanley depth of I n,d for certain values of n and d and a bound for others.…”
Section: Introductionmentioning
confidence: 91%
“…This formula was later confirmed by Biró, Howard, Keller, Trotter and Young in [4] using combinatorial techniques upon which this paper builds. The Stanley depth of I n,d in the other situation remains unexplored in general, although Cimpoeas ¸considered a similar problem in [7]. In this paper, we prove an exact formula for the Stanley depth of I n,d for certain values of n and d and a bound for others.…”
Section: Introductionmentioning
confidence: 91%
“…But then sdepth I j ≥ p + 1. In fact, Cimpoeaş [4,Corollary 1.5] showed that the Stanley depth of any Z n -graded torsionfree S-module is at least 1. Hence the asserted inequality for the Stanley depth of I j follows from [8,Lemma 3.6].…”
Section: Stanley Depth Of Syzygiesmentioning
confidence: 99%
“…Remark 3.6. In [4] it is shown that the Stanley depth of the squarefree Veronese ideal generated by squarefree monomials of degree d has Stanley depth less or equal to…”
mentioning
confidence: 99%
“…where each u i ∈ M is homogeneous, and Z i is a subset of {x In [20], Stanley conjectures that depth M ≤ sdepth M for all finitely generated Z ngraded S-module M. Although this conjecture remains open in general, it has been confirmed in several special cases, see, for example, [1][2][3], [5][6][7][8][9][10][11][12], [17] and [18]. In [11], Herzog, Vladoiu and Zheng proved that the Stanley depth of M = I/J can be computed in finite number of steps, where J ⊂ I are monomial ideals of S. They associated I/J with a poset P I/J and showed that the Stanley depth of I/J is determined by partitioning P I/J into suitable intervals.…”
Section: Introductionmentioning
confidence: 99%